2019
DOI: 10.1103/physrevb.99.085429
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and electronic properties of heterostructures of MXene and graphene

Abstract: MXene-based heterostructures have received considerable interest owing to their unique properties. Herein, we examine various heterostructures of the prototypical MXene Ti3C2T2 (T=O, OH, F; terminal groups) and graphene using density functional theory. We find that the adhesion energy, charge transfer, and band structure of these heterostructures are sensitive not only to the surface functional group, but also to the stacking order. Due to its greatest difference in work function with graphene, Ti3C2(OH)2 has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…A WF of 4.37 eV has been reported for Ti 3 C 2 T x and was observed to form a Schottky barrier with n-Si, which performed as an electrode and depicted charge carrier migration and separation . Furthermore, the composite of Ti 3 C 2 T x with graphene has been explored in many studies for various applications by taking advantage of the WF . For instance, in a current study, Ti 3 C 2 T x was studied to show various WFs because of the terminations, leading to the change in the path of electron mobility and rate of migration of electrons and inducing polarization on the junction of the composite.…”
Section: Overview and Fundamentals Of Mxenementioning
confidence: 92%
“…A WF of 4.37 eV has been reported for Ti 3 C 2 T x and was observed to form a Schottky barrier with n-Si, which performed as an electrode and depicted charge carrier migration and separation . Furthermore, the composite of Ti 3 C 2 T x with graphene has been explored in many studies for various applications by taking advantage of the WF . For instance, in a current study, Ti 3 C 2 T x was studied to show various WFs because of the terminations, leading to the change in the path of electron mobility and rate of migration of electrons and inducing polarization on the junction of the composite.…”
Section: Overview and Fundamentals Of Mxenementioning
confidence: 92%
“…Tahini et al further found that the 2p band center of terminal group T has a “volcano” relation with the work function, which enables the work function modulation by surface engineering for specific applications . The large tunability of MXene’s work function enables broader applications, such as semiconductor/metal heterojunctions …”
Section: Intrinsic Properties Of Mxenesmentioning
confidence: 99%
“…The interlayer distance is set to be 1.42 nm according to the XRD results. It is noteworthy that the binding energy is closely related to the interlayer distance. , The resulting interlayer binding energies between different termination species are shown in Figure e. The interaction energies between Ti 3 C 2 F 2 and different terminated Ti 3 C 2 T x are <0.11 eV nm –2 .…”
mentioning
confidence: 96%